Feeding Practices and Nutritional Status of Children under Five Years Attending at Selected Child Welfare Centre, Dhaka Cantonment (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Malnutrition is one of the catastrophes on human life and a major public health problem. Children below five years of age are at-risk population and hence malnutrition is the leading cause for morbidity and mortality among them. Feeding practices play a pivotal role in determining the nutritional status of Children.Objectives: To find the nutritional status of under-five children and to assess whether infant feeding practices are correlated with nutritional status.Materials and Methods: This cross-sectional study was carried out from 01 March to 30 June 2012 among 110 conveniently and randomly selected children and their mothers as respondents attending selected child welfare centre (CWC) of Dhaka Cantonment. An electronic weighing scale, a standard height scale and a predesigned structured questionnaire were used. All data were analyzed by SPSS. Association was assessed with Chi square test. The prevalence of malnutrition was assessed by different indices of nutritional status based on Weight for Age Zscore (WAZ), Height for Age Z-score (HAZ) and Weight for Height Z -Score (WHZ).Results: Mean age of study population was 31.3±16 months. Out of total 110 mothers as respondents 62 (56.4%) mothers fed their child colostrum. Majority of the mothers (81.7.0%) exclusively breastfed their child. Most of the mothers (59.1%) did not provide proper complementary feeding and 37.3% mother fed their child pre lacteal feeding. Total underweight children were 32 (29%), total stunted children were 44(40.0%) and total wasted children were 26(23.6%). The prevalence of Stunting was higher among children who had not exclusively breastfed. This study showed that the relationship of pre-lacteal feeding and complementary feeding with WAZ, HAZ and WAZ were statistically significant.Conclusion: This study might serve as an initiative to identify the influences of feeding practices on children’s nutritional status to promote and protect the optimal feeding practices for improving nutritional status of children under five years.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 54-56